O apoxeo dos escudeiros na Galiza baixomedieval : o caso de Vilariño : o seu património e parentelas - Piñeyro Maseda, Pablo S. Otero (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
The social heterogeneity and importance of those admitted as “squires” demonstrates the importance of collecting more information about their patrimony, ancestry, allegiance, relatives and course of life, to fully understand the historical context in which they lived in. Therefore, the study of the particular case of the Vilariño family provides us with the elements to a broader overview of this selective process during the late Middle Ages in Galicia. This family from Orense, with possible kinship ties with Portuguese noblemen, served the powerful Sarmiento family as squires.